2004
DOI: 10.1097/00006231-200412000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Development of 99mTc-neomannosyl human serum albumin (99mTc-MSA) as a novel receptor binding agent for sentinel lymph node imaging

Abstract: We have successfully developed a novel 99mTc-MSA for lymphoscintigraphy. The results of animal studies show that 99mTc-MSA has promising properties for SLN imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…RGD derivatives have been used to investigate a v b 3 integrin expression in vascular and tumor angiogenesis by biologic and clinical researchers (24)(25)(26)(27)(28)(29). In addition, a mannose and stearylamine conjugate (Man-C 18 ) was synthesized to target the mannose receptor of Kupffer cells (30)(31)(32)(33), and a lactose and stearylamine conjugate (Lac-C 18 ) was synthesized to target the asialoglycoprotein receptor in the liver (32,34,35). For radiolabeling with 68 Ga, we conjugated the bifunctional chelating agent SCN-Bz-NOTA to stearylamine (NOTA-C 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…RGD derivatives have been used to investigate a v b 3 integrin expression in vascular and tumor angiogenesis by biologic and clinical researchers (24)(25)(26)(27)(28)(29). In addition, a mannose and stearylamine conjugate (Man-C 18 ) was synthesized to target the mannose receptor of Kupffer cells (30)(31)(32)(33), and a lactose and stearylamine conjugate (Lac-C 18 ) was synthesized to target the asialoglycoprotein receptor in the liver (32,34,35). For radiolabeling with 68 Ga, we conjugated the bifunctional chelating agent SCN-Bz-NOTA to stearylamine (NOTA-C 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, 99m Tc-neomannosyl human serum albumin (MSA) was developed for lymphoscintigraphy or imaging sentinel lymph nodes (Takagi et al, 2004;Jeong et al, 2004b). The terminal mannose residues of MSA bind to the mannose receptors of lymph nodes after subcutaneous or intradermal injection (Takagi et al, 2004;Jeong et al, 2004b;Vera et al, 2001aVera et al, , 2001b.…”
Section: Introduction 99mmentioning
confidence: 99%
“…The terminal mannose residues of MSA bind to the mannose receptors of lymph nodes after subcutaneous or intradermal injection (Takagi et al, 2004;Jeong et al, 2004b;Vera et al, 2001aVera et al, , 2001b. It has been reported that mannosylated bovine serum albumin rapidly binds to Kupffer cells and endothelial cells in the liver when injected into rat intravenously due to the presence of mannose receptor (Magnusson and Berg, 1989;Ogawara et al, 1999).…”
Section: Introduction 99mmentioning
confidence: 99%
“…Methods previously described in the literature were used to synthesize MSA from human serum albumin (13,19), RITC-MSA (15), and NOTA-MSA for 68 Ga labeling (17). The labeling efficiency and radiochemical purity determined by instant thin-layer chromatography silica gel were always greater than 98%.…”
Section: Methodsmentioning
confidence: 99%
“…Neomannosylated human serum albumin (MSA) was developed initially for lymphoscintigraphy and imaging of the sentinel lymph nodes (12,13) based on the binding of the terminal mannose residues of MSA to the specific MRs of the lymph nodes. When intravenously injected into rats, mannosylated bovine serum albumin rapidly binds to the Kupffer and endothelial cells in the liver because of the presence of MRs on these cells (14,15).…”
mentioning
confidence: 99%